Developing Teachers' Paradigms for Applying Pedagogical Content Knowledge Skills in Implementing the Deep Learning Curriculum at the Junior High School Level - Hastuti; Sukirman (Universitas Islam Negeri Palopo, 2025)
The successful implementation of the Deep Learning Curriculum requires teachers to possess not only strong subject-matter expertise but also the ability to transform knowledge into meaningful learning experiences through Pedagogical Content Knowledge (PCK). However, limited research has examined how teachers develop their paradigms for applying PCK skills within the context of curriculum reform, particularly at the junior high school level in Indonesia. This study aimed to explore how teachers develop their paradigms for applying PCK skills in implementing the Deep Learning Curriculum. A qualitative descriptive design was employed, involving three junior high school teachers from three different subject areas (English, Science, and Mathematics). Data were collected through semi-structured interviews, classroom observations, and document analysis, and were analyzed using thematic analysis involving data reduction, coding, categorization, and theme development. The findings revealed six major themes: (1) PCK as the integration of content mastery and pedagogical transformation; (2) contextualization and student-centered learning as core pedagogical principles; (3) deep learning as meaningful, reflective, and contextual learning; (4) the shift from teacher-centered to student-centered instructional paradigms; (5) challenges in implementing PCK and deep learning, including diverse student needs, limited instructional time, administrative workload, technological constraints, and the influence of artificial intelligence; and (6) collaborative professional learning as a driver of teacher growth. Teachers had begun to reconstruct their instructional paradigms by emphasizing critical thinking, inquiry, contextual learning, and student engagement; however, the effectiveness of implementation remained influenced by structural, pedagogical, and institutional challenges. This study concludes that the development of teachers' paradigms for applying PCK skills is a continuous professional process that requires reflective practice, collaborative learning, and sustained institutional support. The findings contribute to the growing literature on PCK and curriculum reform by clarifying how teachers navigate pedagogical transformation during the implementation of the Deep Learning Curriculum, and they offer practical implications for teacher professional development programs aimed at strengthening PCK and supporting meaningful learning in contemporary educational contexts.